Unframing existence: an ethical and theological appropriation of Heidegger's critique of modernity - Atkins, Z (2014)
This thesis argues that Heidegger’s thought offers crucial insights into the structural challenges that modernity poses to being an ethical and religious person. I argue that these difficulties come down to an instrumentalist conception of truth, a denial or repression of finitude as the condition of meaningfulness, and a philosophical anthropology that is both too subjectivistic and too objectivistic. Yet while Heidegger was good on the diagnosis, he was reluctant to give more than digressive and opaque prescriptions to these problems. My thesis seeks to respond to this lacuna by putting Heidegger’s critical observations in the service of articulating a positive religious ethics. To that end, it seeks to locate—as well as redefine from an ontological perspective—the human dispositions and practices that expose truth in a non-instrumental light, that show finitude as a positive condition of meaningfulness, and that reveal the essence of the human being in non-subjectivist and non- objectivist terms. I argue that these include listening and gratitude—dispositions and practices I claim should form the backbone of any religious ethics, and yet which I also claim should not be limited to those who believe in a personal, theistic God. My thesis contributes to the fields of modern theology and Heidegger Studies in four ways. First, it shows that Heidegger’s critics (such as Levinas and Adorno) are wrong to oppose ontology to ethics. Second, it shows that Heidegger’s critics (such as Marion and Jonas) are wrong to oppose ontology to theology. Third, it shows that Heidegger’s own ambivalence about the ethical and theological relevance of his thought allows for the development of a deeply ethical and theological posture. And fourth, it offers a unique, post-Heideggerian interpretation of gratitude, one in which it is understood as a structure of Dasein that is both “always already” and “not yet” operative.